ABOUT SOME HISTORICAL EXTREME TABLES AND THEIR PROOF - Aroyev Dilshod Davronovich; Sobirova Subiniso Muxsinjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents methods to prove the Geron issue, which has many practical significance